Burnout syndrome and working conditions in nursing professionals in a surgical center of a national hospital in Peru in the context of COVID-19 - Vergara Mejía, Angélica Genoveva (2025)
Burnout syndrome affects nursing professionals and its relationship with working conditions is crucial. Objective:. Determine the association between SB and working conditions in nurses in a Peruvian hospital during 2020, in the context of COVID-19. Research. Prospective and analytical study, using the Maslach Burnout Inventory and a validated questionnaire on working conditions. Data were analyzed with association tests. Findings. Of 88 nurses, 12% had BS; 42,1% considered their working conditions adequate. A significant association was found between SB and global conditions of the work environment (p < 0,001). An increase in the working conditions score reduced the tendency (PR = 0,83; CI = 0,73-0,94; p = 0,004) and presence (PR=0.65; CI = 0,56-0,76; p < 0,001) of SB. Conclusions. Improving working conditions is positively linked to a decrease in SB in nurses in surgical centers.